Inuvik Regional Hospital - Digital Library North; Stobbs, Robyn (2014)
Located at 285 - 289 Mackenzie Road, in Inuvik and operate by the Beaufort Delta Health & Social Services, the Inuvik Regional Hospital has 51 beds. The Inuvik Regional Hospital offers: Emergency Services, Acute Care, Diagnostic Imaging, Laboratory Services, Long Term Care, Rehabilitation, Health Promotion, Obstetrical Care, Operating Room, Pharmacy, Physician Family Clinics, Visiting Specialist Clinics, and a Medical Social Worker.